Stability Analysis and Cost Benefit Analysis of the Extension Retaining Wall for Kenyir Dam Spillway - Hassani A.; Melan A.; Zawawi M.H.; Syamsir A.; Azman S.; Radzi M.R.M.; Sabri S. (Springer, 2023)
Retaining wall is a structure that are designed and constructed to withstand lateral pressure acting on it. It also plays a huge role to channel the water to the safe area that can minimize the impact of vortex phenomena. This paper is comparing the stability analysis and cost benefit analysis between two types of retaining wall that proposed to be an extension wall to the existing spillways retaining wall at Kenyir Dam:- (i) gabion wall and (ii) reinforced concrete retaining wall (RC wall). The optimized dimension and layout for both type of retaining wall is presented in this paper considering the stability analysis requirements. Other than that, cost benefit analysis is conducted in order to compare the most effective cost between these two type of walls. It is found that the price for gabion wall is lower than RC wall considering the replacement of the gabion wall after 10 years. 2020, Springer Nature Singapore Pte Ltd.